Respuesta :
Answer: [tex]2[\ln(x-1)-\ln(x+1)][/tex]
Step-by-step explanation:
We know that , the properties of logarithm are:
P[1] [tex]\log (ab)= \log a+\log b[/tex]
P[2] [tex]\log(\dfrac{a}{b})=\log a-\log b[/tex]
P[3] [tex]\log a^n= n\log a[/tex]
The given expression in terms of Natural log : [tex] \ln (\dfrac{x-1}{x+1})^{2}[/tex]
[tex]=2\ln ((\dfrac{x-1}{x+1})[/tex] [ By using P[3]]
[tex]=2[\ln(x-1)-\ln(x+1)][/tex] [ By using Property (1)]
Hence, the simplified expression becomes [tex]2[\ln(x-1)-\ln(x+1)][/tex] .
We can use two properties to solve:
Quotient Rule: [tex]\text{ln}\frac{x}{y} = \text{ln}(x)-\text{ln}(y)[/tex]
Power Rule: [tex]\text{ln}(x)^p = p~\text{ln}(x)[/tex]
Simplify the expression using the power rule:
In(x - 1/x + 1)^2 → 2 ln (x - 1/x + 1)
Simplify using the quotient rule:
2 ln (x - 1/x + 1) → 2[ln(x - 1) - ln(x + 1)]
Therefore, the the simplified logarithm is 2[ln(x - 1) - ln(x + 1)]
Best of Luck!